2020
DOI: 10.1177/0040517520912478
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/ultra-high molecular weight polyethylene partially absorbable suture with improved mechanical performances for tendon and ligament repair

Abstract: Orthopedic suture, as an implantable surgical device for skeletal and soft tissue connection, is vital in tendon or ligament injury repair. Resorbable therapy approaches exhibit excellent biocompatibility in the field of suture materials but lack a long-term fixation effect in orthopedic treatment. Herein, this study focused on a series of partially absorbable orthopedic sutures, which were composed of absorbable polycaprolactone (PCL) multifilament and non-absorbable ultra-high molecular weight polyethylene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The obtained results constitute a beneficial creep behavior taking into account the desired application of the presented medical device, which should endure load application over extended time without becoming lax. The creep deformation of a structure will result in gap formation or even failure of the repair, so by minimizing elongation, it is possible to reduce gap formation and increase the repair of the tissue 59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results constitute a beneficial creep behavior taking into account the desired application of the presented medical device, which should endure load application over extended time without becoming lax. The creep deformation of a structure will result in gap formation or even failure of the repair, so by minimizing elongation, it is possible to reduce gap formation and increase the repair of the tissue 59 …”
Section: Resultsmentioning
confidence: 99%
“…The creep deformation of a structure will result in gap formation or even failure of the repair, so by minimizing elongation, it is possible to reduce gap formation and increase the repair of the tissue. 59 There are a few examples of commercialized fibrous devices made of PET (e.g., Leeds-Keio Ligament and Lars Ligament) with adequate initial mechanical strength. However, it is reported that these nondegradable devices generally fail due to the long-term mechanical phenomena such as creep, fatigue, stress shielding, and permanent deformation.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [ 190 ] reported that UHMWPE filament could be modified with polycaprolactone for ligament and tendon regeneration [ 191 ]. Absorbable polycaprolactone PCL has attracted mainstream attention in recent years for the development of tendon/ligament repair materials due to its excellent performance attributes of low degradation, high stability, non-toxicity, and bioresorbability [ 192 ].…”
Section: Relationship Between Human Ligament and Uhmwpementioning
confidence: 99%
“…Absorbable polycaprolactone PCL has attracted mainstream attention in recent years for the development of tendon/ligament repair materials due to its excellent performance of degradation, high stability, non-toxicity, and bioresorbability [138]. Fibrous PCL has also been reported to be able to help cell growth [139]. C.C Schmidt et al reported that growth factors play an essential role in the stimulation of fibroblast division and ligament healing.…”
Section: Common Biomaterials For Uhmwpe Graft Modificationmentioning
confidence: 99%